Breathable and Flexible Dual‐Sided Nonwovens with Adjustable Infrared Optical Performances for Smart Textile. (20th October 2021) - Gao, Qiang; Lauster, Tobias; Kopera, Bernd A. F.; Retsch, Markus; Agarwal, Seema; Greiner, Andreas
Abstract: Maintaining constant body temperature is the most basic function of textiles. However, traditional fabrics irradiate a massive amount of thermal energy to the ambient environment due to the high emissivity of the materials used for textiles. This phenomenon weakens the thermal function, causing vast thermal energy loss by dissipation as infrared (IR) irradiation. To improve thermal comfort and reduce extra energy consumption, smart thermal management textiles must maintain constant body temperature by regulating IR irradiation from the human body or by compensating heat losses by joule heating. Here, a smart dual‐sided nonwovens' preparation procedure and properties for use as a textile with this combination of properties are shown. The nonwoven combines a high porosity with high IR reflectance and low IR emittance. The nonwoven is adjustable from reflective to emissive when turned inside out. It is consequently permeable to air and vapor and simultaneously mitigates thermal heat losses with radiation. In addition, low sheet resistance and superior flexibility make it possible to use them in flexible electronics and wearable devices. It can be further equipped with a porous Joule heating layer adding active control to the personal thermal comfort. Abstract : A breathable and flexible dual‐sided nonwoven composed of polyimide nanofiber and silver nanowires possesses good electrical conductivity and high infrared reflection performance. A personal thermal management device is constructed of two layers of dual‐sided nonwoven containing different amounts of silver nanowires, demonstrating prominent human body warming performance by combining active Joule heating and passive warming via reduced radiative losses.